2018
DOI: 10.1002/jia2.25199
|View full text |Cite
|
Sign up to set email alerts
|

Repeated rectal application of a hyperosmolar lubricant is associated with microbiota shifts but does not affect PrEP drug concentrations: results from a randomized trial in men who have sex with men

Abstract: IntroductionOral pre‐exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate (TDF) and emtricitabine (FTC) is highly effective in preventing HIV infection among men who have sex with men (MSM). The effects of consistent personal lubricant use in the rectum on tissue PrEP drug concentrations and the rectal microbiota are unknown. We investigated rectal PrEP drug concentrations and the microbiota in MSM before and after repeated rectal application of a hyperosmolar lubricant.MethodsWe randomized 60 HIV‐ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(63 reference statements)
2
8
0
Order By: Relevance
“…We found very little bacterial protein-based compositional similarity between matching neovaginal and rectal profiles based on bacterial proteins measured, although we were underpowered to properly evaluate this comparison. The rectal microbial profiles observed in our study were similar to those of other studies particularly those that examined rectal/anal microbiomes of CW as well as men who have sex with men where Prevotella and Bacteroides were most abundant [24][25][26].…”
Section: Discussionsupporting
confidence: 84%
“…We found very little bacterial protein-based compositional similarity between matching neovaginal and rectal profiles based on bacterial proteins measured, although we were underpowered to properly evaluate this comparison. The rectal microbial profiles observed in our study were similar to those of other studies particularly those that examined rectal/anal microbiomes of CW as well as men who have sex with men where Prevotella and Bacteroides were most abundant [24][25][26].…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with prior evidence that neutrophils and IL-17-producing cells are important inflammatory mediators within the gastrointestinal (GI) mucosa [16,17]. We also discovered a microbiome that was enriched for the Prevotellaceae over Bacteroidaceae family, and in another study [18], that repeated rectal hyperosmolar lubricant application was associated with a microbiome shift favouring Prevotellaceae over Bacteroidaceae. We hypothesize that this distinct rectal mucosal immune milieu could be attributed to repeated mucosal immune responses to intercourse with antigenic mucosal exposure to the gut microbiome during intercourse and/or semen exposure, and/or rectal product use [19,20].…”
Section: Introductionsupporting
confidence: 91%
“…Many of these lubricants are hyperosmolar and have been linked to epithelial damage in the distal colon as well as to an increased risk of acquisition of rectal gonorrhea and chlamydia [117,118]. A small study of MSM randomized to apply daily hyperosmolar rectal lubricant (N = 20), take daily oral pre-exposure prophylaxis (PrEP) (N = 19) or both (N = 21) for 7 days found that lubricant users had a decrease in the genus Bacteroides (p = 0.01) and a non-significant increase in the genus Prevotella (p = 0.09) in rectal mucosal swabs [119]. There is no other available data on this topic to our knowledge.…”
Section: Non-us/europementioning
confidence: 99%